A Study on the Impact of Derivatives on Firm Value - Rathnasamy, Kiruthiga (2008)
Abstract In today's globalized era all firms face an assortment of exchange rate risk in the due course of their normal business. In this context, the usage of financial derivatives as an integral part of the corporate risk management has afforded the managers of large corporation with a whole range of derivative instruments to mitigate the risk or even to add value to the firm.